Performance evaluation of a bilayer SPR-based fiber optic RI sensor with TiO2 using FDTD solutions - Al-Qazwini, Yusser; Muhammad Noor, Ahmad Shukri; Yadav, T. K.; Yaacob, Mohd. Hanif; Harun, Sulaiman Wadi; Mahdi, Mohd Adzir (SpringerOpen, 2014)
We proposed a new bilayer surface plasmon resonance-based fiber-optic refractive index sensor with silver and an over-layer of TiO2. We numerically investigated the optimal thickness of TiO2 over-layer in the proposed sensor and compared its performance to that based on typical bimetallic layers of silver-and-gold in the aqueous media using finite-difference time domain approach. We show that the use of TiO2 over-layer greatly improves the sensor performance in terms of sensitivity and signal-to-noise ratio compared to that with gold as the over-layer. Not only does the TiO2 over-layer offer a cost-effective alternative to gold for overcoming the oxidation problem, but also it allows resonance wavelength-tunability.